Children's informed signified and voluntary consent to heart surgery: Professionals' practical perspectives. (June 2022) - Alderson, Priscilla; Bellsham-Revell, Hannah; Brierley, Joe; Dedieu, Nathalie; Heath, Joanna; Johnson, Mae; Johnson, Samantha; Katsatis, Alexia; Kazmi, Romana; King, Liz; Mendizabal, Rosa; Sutcliffe, Katy; et al.
Background: The law and literature about children's consent generally assume that patients aged under-18 cannot consent until around 12 years, and cannot refuse recommended surgery. Children deemed pre-competent do not have automatic rights to information or to protection from unwanted interventions. However, the observed practitioners tend to inform young children s, respect their consent or refusal, and help them to "want" to have the surgery. Refusal of heart transplantation by 6-year-olds is accepted. Research question: What are possible reasons to explain the differences between theories and practices about the ages when children begin to be informed about elective heart surgery, and when their consent or refusal begins to be respected? Research design, participants and context: Research methods included reviews of related healthcare, law and ethics literature; observations and conversations with staff and families in two London hospitals; audio-recorded semi-structured interviews with a purposive sample of 45 healthcare professionals and related experts; interviews and a survey with parents and children aged 6- to 15-years having elective surgery (not reported in this paper); meetings with an interdisciplinary advisory group; thematic analysis of qualitative data and co-authorship of papers with participants. Ethical considerations: Approval was granted by four research ethics committees/authorities. All interviewees gave their informed written consent. Findings: Interviewees explained their views and experiences about children's ages of competence to understand and consent or refuse, analysed by their differing emphases on informed, signified or voluntary consent. Discussion: Differing views about children's competence to understand and consent are associated with emphases on consent as an intellectual, practical and/or emotional process.Conclusion : Greater respect for children's practical signified, emotional voluntary and intellectual informed consent can increase respectful understanding of children's consent. Nurses play a vital part in children's practitioner-patient relationships and physical care and therefore in all three elements of consent.